Effect of consuming different dairy products on calcium, phosphorus and pH levels of human dental plaque: A comparative study - Ravishankar, T. L.; Yadav, V.; Tangade, P. S.; Tirth, A.; Chaitra, T. R. (European archives of paediatric dentistry, 2012)
AIM: To determine the calcium, phosphorus and pH levels of human dental plaque after consuming different dairy products. METHODS: 68 students (34 with caries and 34 caries-free) aged 17–20 years from a private dental college, Moradabad city, who agreed to refrain from oral hygiene procedures for 48 hours were selected for the study. Calcium and phosphorus levels of harvested dental plaque were measured using an electrolyte analyser while plaque pH was measured using a digital pH meter after consuming different dairy products (cheese, milk, yogurt) and compared with the control (paraffin) group. RESULTS: Cheese and yogurt groups showed a statistically significant rise in mean plaque concentrations of calcium and phosphorus, whereas milk and control groups showed the least rise in plaque concentrations for both caries-active and caries-free subjects. Plaque pH showed a stronger correlation with plaque calcium and phosphorus concentrations in both caries-active and caries-free subjects. CONCLUSION: Cheese and yogurt without any added sugar (sucrose) are non-cariogenic and to some extent cariostatic as they increase calcium and phosphorus concentration in dental plaque. Dairy products without added sugar can be recommended as after meal desserts, especially to school children, which would help to reduce the incidence of dental caries.